Neuroprotection during aortic surgery. Issue 3 (September 2016) - Lindsay, Helen; Srinivas, Coimbatore; Djaiani, George
Abstract : Neurological injury is a major limitation of aortic surgery, whether it involves spinal cord injury following intervention to the thoracoabdominal aorta, or stroke following surgery on the arch and ascending aorta. Despite an extensive body of literature and various proposals, a completely effective strategy to prevent or treat neurological injury remains elusive. In this article, we summarise the evidence for established and emerging strategies, and review current concepts in pathophysiology and risk assessment as they relate to neurological injury.